Research on the Interaction between Innovation and Port-City Economic System: A Case from China - Zhen Chen (Discrete Dynamics in Nature and Society)
Port city is the node in global commodity flows. It is open to the outside world and often the primary test field of new economic development model. To reduce the negative impact of the global economic crisis since 2008, various developing patterns have been tested in the port city. And the most effective way should rely on the city’s operation mechanism. Here a System Dynamics model is established to analyze the interaction process of the elements in the port-city system. Then choose Shenzhen city as the empirical case. By changing the proportion of R&D and fixed-asset investment, the impact of different economic measures on the system could be confirmed. The result shows that, in order to stabilize the port city’s economic growth, it should change the traditional development pattern to the innovation driven one. The former focuses on facilities investment and capacity expansion. The latter aims at port efficiency promoting and port business value increases.